Technology Enterpreneurship (ENT600) Blueprint Ceiling Fan Cleaner / Nursyafreena Rosli - Mohd Zaki, Nur Namirah (2020)
Our company offers a new product call the Ceiling Fan Cleaner. Our product is suitable for households. Our product also simple, light and effective to be use. The design of our product can attract buyers to buy it. The price also affordable and reasonable so that the users do not feel burden to buy this product. The design and quality of the product will evolves based on consumer trends and demands of the customers.